Improvement of bi-layered YBCO superconducting films by using Ag and Au interlayers. Issue 3 (15th February 2020) - Wang, Linli; Qu, Timing; Feng, Feng; Zou, Shengnan; Yang, Zhirong; Ma, Zengxian; Feng, Pingfa
Abstract: Chemical solution deposition is a promising technology to fabricate YBCO superconducting thin films due to its low-cost advantage. However, the decreasing of critical current density ( J c ) usually occurred in the fabrication of multi-layered YBCO films. In this study, Ag and Au heterogeneous interlayers were fabricated by using sputtering deposition in order to improve the bi-layered YBCO films, and the influence of crystallization temperature from 740 ∘ C to 800 ∘ C was investigated. It was found that J c could be enhanced by both interlayers relative to the counterparts without interlayers, and the effect of Ag interlayer was superior to that of Au interlayer. When the crystallization temperature was 800 ∘ C, the optimal sample with Ag interlayer had a J c 3.65 MA/cm 2, which was about twice of the J c of its counterpart. The surface morphologies and cross-sections were observed by using scanning electron microscope, and the content variations of c -axis oriented grains were measured by using Raman spectroscopy, which could help to investigate the influences of interlayers on the microstructure of YBCO films. The possible reasons for the improvement effects of Ag and Au interlayers were discussed based on the experimental results.